232k views
4 votes
Which function is the inverse of y = -3x + 6/7?

a; y = -1/3x + 18/7
b: y = -1/3x + 7/6
c: y = -3x - 6/7
d: y = -1/3x + 2/7

User Bleu
by
4.5k points

2 Answers

4 votes

Answer:

D

Explanation:

Swap x for y and y for x. Then solve the equation for y.

User Joell
by
4.9k points
3 votes

Answer:

option D

y = -1/3x + 2/7

Explanation:

y = -3x + 6/7

Step1

Interchange the variables

x = -3y + 6/7

Step2

Solve for y

x - 6/7 = -3y

y =
((6)/(7)-x )/(3)

step3

Solve for y and replace with f−1(x)


f^(-1)(x)=
((6)/(7)-x )/(3)

step4

simplify


y ={(6)/(7(3))-(x)/(3)}

=
{(2)/(7)-(x)/(3) }

User ChristianM
by
4.6k points